IMMU-36. B CELL-VACCINE ELICITS LONG TERM IMMUNITY AGAINST GLIOBLASTOMA VIA ACTIVATION AND DIFFERENTIATION OF TUMOR-SPECIFIC CD8+ MEMORY T CELLS. (12th November 2021) - Hou, David; Castro, Brandyn; Dapash, Mark; Rashidi, Aida; Zhang, Peng; Han, Yu; Lopez-Rosas, Aurora; Lesniak, Maciej; Miska, Jason; Chang, Catalina
Abstract: While immunotherapy is used clinically to treat many cancers, its translation into brain tumors remains elusive. The importance of B cells in cancer immunity has become increasingly clear, and we previously developed a B cell-based cellular vaccine (BVax ) against glioblastoma (GBM) by further activating 4-1BBL + B cells with CD40 agonism and IFNγ. BVax were characterized as professional antigen-presenting cells (APCs) that promote CD8 + T cell migration and persistence in murine tumor-bearing brains. This study seeks to understand the mechanisms underlying BVax -induced CD8 + T cell fitness in the tumor microenvironment. Initial transcriptomic analysis highlighted that Bvax express high levels of IL15Rα, indicating their potential ability to trans-present IL15. Considering IL15 trans-presentation is fundamental in T-cell memory differentiation, we used BVax to induce T cell activation in the presence of exogenous IL15. BVax were better capable of activating antigen-specific CD8 + T cells and promoting a memory phenotype when compared to other professional APCs such as dendritic cells (DCs). T cell receptor (TCR) CDR3β sequencing showed that BVax expanded a number of TCR clones in-vitro that were found in brains of CT2A tumor-bearing mice in-vivo . These BVax -activated CD8 + T cells displayed a stronger antigen recall response and unique metabolic profile compared to DC-activated CD8 + T cells as shown by metabolomic analysis of tumor-infiltrating CD8 + T cells. When comparing the anti-tumor effects of CD8 + T cells activated by various APCs, BVax with exogenous IL15 promoted CD8 + T cells that displayed the most potent cytotoxicity against GBM cells in-vitro . Collectively, this study suggests that the IL15/IL15Rα axis and interactions with CD8 + T cell are key factors of BVax therapy in promoting a robust survival benefit and long-term immunologic memory against GBM in preclinical models. Additionally, the development of T cell therapies based on B cell licensing can be a promising future approach for glioblastoma therapy.